Transformed Securities and Alternative Factor Structures - Huang, Roger D.; Jo, Hoje (Journal of Finance, 1992)
Grinblatt and Titman (1985) reformulate a result of Chamberlain and Rothschild (1983) to show that the approximate factor structure of Chamberlain and Rothschild is asymptotically equivalent to the strict factor structure of Ross (1976) as long as investors can always repackage securities into an equal number of arbitrary portfolios. This paper uses a Procrustes rotation methodology that is compatible with the repackaging interpretation of Grinblatt and Titman to show that the empirical structure of stock prices is consistent with the convergency hypothesis.